Revisiting the Role of TGFβ Receptor Internalization for Smad Signaling: It is Not Required in Optogenetic TGFβ Signaling Systems. Issue 10 (31st August 2021) - Li, Yuchao; Lee, Heeyoung; Heo, Won Do; Zi, Zhike
Abstract: Endocytosis is an important process by which many signaling receptors reach their intracellular effectors. Accumulating evidence suggests that internalized receptors play critical roles in triggering cellular signaling, including transforming growth factor β (TGFβ) signaling. Despite intensive studies on the TGFβ pathway over the last decades, the necessity of TGFβ receptor endocytosis for downstream TGFβ signaling responses is a subject of debate. In this study, mathematical modeling and synthetic biology approaches are combined to re‐evaluate whether TGFβ receptor internalization is indispensable for inducing Smad signaling. It is found that optogenetic systems with plasma membrane‐tethered TGFβ receptors can induce fast and sustained Smad2 activation upon light stimulations. Modeling analysis suggests that endocytosis is precluded for the membrane‐anchored optogenetic TGFβ receptors. Therefore, this study provides new evidence to support that TGFβ receptor internalization is not required for Smad2 activation. Abstract : The necessity of TGFβ receptor endocytosis for Smad2 signaling is much debated. This study revisits this issue using optogenetic TGFβ signaling systems with plasma membrane‐tethered TGFβ receptors. Mathematical modeling and experimental analyses show that Smad2 signaling can be efficiently induced from the plasma membrane, which supports that TGFβ receptor internalization is not required for Smad2 activation.